2021
DOI: 10.1016/j.jcmgh.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microphysiological Colon Platform to Decipher Mechanisms Driving Human Intestinal Permeability

Abstract: Colon Intestine-Chip Q9 (Emulate, Inc, Boston, MA), seeded with human colon crypt-derived epithelial and primary microvascular endothelial cells, was built to investigate leaky gut in human beings. This ex vivo platform recapitulated the effects of proinflammatory cytokines in the intestinal epithelial barrier and identified novel mechanisms of action. BACKGROUND & AIMS:The limited availability of organoid systems that mimic the molecular signatures and architecture of human intestinal epithelium has been an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 63 publications
(98 reference statements)
2
25
0
1
Order By: Relevance
“…The addition of IL‐22, which has been implicated in the pathogenesis of IBD and is generally thought to support the epithelial barrier, 17–19 showed, as anticipated, that IL‐22 induced STAT3 activation in a concentration‐ and time‐dependent manner. However, unexpectedly, IL‐22 compromised epithelial morphology and induced apoptosis 15 . These data show the importance of using more in vivo‐ like and species‐specific experimental models to understand human diseases.…”
Section: High Content Screening With Organoidsmentioning
confidence: 83%
See 3 more Smart Citations
“…The addition of IL‐22, which has been implicated in the pathogenesis of IBD and is generally thought to support the epithelial barrier, 17–19 showed, as anticipated, that IL‐22 induced STAT3 activation in a concentration‐ and time‐dependent manner. However, unexpectedly, IL‐22 compromised epithelial morphology and induced apoptosis 15 . These data show the importance of using more in vivo‐ like and species‐specific experimental models to understand human diseases.…”
Section: High Content Screening With Organoidsmentioning
confidence: 83%
“…She showed that coculture of endothelial and epithelial cells recreated human colon physiology more closely than do classical organoids, with enhanced formation of a tight junction network and epithelial polarity (Figure 1). Applying mechanical force to the Colon‐Chips altered transcription, increasing the expression of genes involved in ion, lipoprotein, and water transportation 15 . Apostolou also showed how the Colon Intestine‐Chip responds to factors known to play a role in IBD while providing additional insights into their effects on the colon.…”
Section: High Content Screening With Organoidsmentioning
confidence: 96%
See 2 more Smart Citations
“… 71,92 At the transcriptome level, peristalsis enhanced gene expressions related to ion, lipoprotein, and water transportation, as evidenced in the analysis of organoid-derived epithelial cells on chip. 110 …”
Section: Gut-on-a-chip Merits For Simulating Environmental Cuesmentioning
confidence: 99%